2022
DOI: 10.1200/jco.2022.40.16_suppl.11500
|View full text |Cite
|
Sign up to set email alerts
|

Primary efficacy and safety of letetresgene autoleucel (lete-cel; GSK3377794) pilot study in patients with advanced and metastatic myxoid/round cell liposarcoma (MRCLS).

Abstract: 11500 Background: Lete-cel is an autologous T-cell therapy targeting NY-ESO-1 tumors using a genetically modified, high-affinity T-cell receptor. MRCLS is a sarcoma with poor response to current immunotherapy approaches and limited treatment options. The cancer testis antigen NY-ESO-1 is expressed in 80‒90% of MRCLS tumors, making this a promising target. This report summaries the primary efficacy and safety results of a pilot study of lete-cel in patients (pts) with advanced or metastatic MRCLS. Methods: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In particular, the Phase 1 results with lete-cel have been reported. 29 , 86 , 87 Patients with refractory or relapsed SS were divided into 4 cohorts based on NY-ESO-1 tumour expression and received lete-cel after lymphodepletion. Fifty patients were enrolled and 45 received lete-cel infusion.…”
Section: Emerging Targeted and Cellular Therapiesmentioning
confidence: 99%
“…In particular, the Phase 1 results with lete-cel have been reported. 29 , 86 , 87 Patients with refractory or relapsed SS were divided into 4 cohorts based on NY-ESO-1 tumour expression and received lete-cel after lymphodepletion. Fifty patients were enrolled and 45 received lete-cel infusion.…”
Section: Emerging Targeted and Cellular Therapiesmentioning
confidence: 99%
“…The efficacy and safety of lete-cel have also been previously evaluated in a phase I and a phase II clinical (NCT01343043 and NCT02992743). The preliminary efficacy results of phase I [ 63 , 64 , 65 ] reported impressive responses (50% and 40% objective responses for SS and MLPS, respectively, in patients who had received a high-dose lymphodepletion regimen, including 1 complete response). In addition, responses deepened over time and were durable; responses were ongoing in four patients (two with SS and two with MLPS).…”
Section: Adoptive Cellular Therapies: a New Opening Door In Sarcomasmentioning
confidence: 99%
“…[ 99 ] demonstrated that the persistence and functionality of these adoptively transferred T cells were associated with sustained responses in a significant proportion of patients. Moreover, treatment with an autologous T‐cell therapy targeting NY‐ESO‐1 displayed antitumor activity up to 40% ORR and long median PFS, with an acceptable safety profile in a study that enrolled 23 patients with advanced and metastatic MRCLS [ 100 ]. Similarly, preliminary data suggested that afamitresgene autoleucel, a genetically modified autologous melanoma‐associated antigen 4 (MAGE A4) specific T cell therapy, could induce a prolonged response in heavily pre‐treated patients with advanced MAGE‐A4‐expressing SS and MRCLS [ 101 ].…”
Section: Improving the Treatment Of Patients With Sts Through Immunot...mentioning
confidence: 99%